STRATEGIC CULTURE AND INTER-STATE RELATIONS: A CASE OF PAKISTAN AND INDIA (Margalla Papers, 2022)
Geography, culture and history play a central role in shaping a nation's perceptions, biases and images of adversaries. The combination of these factors constitutes strategic culture. Strategic communities tend to adopt diverse approaches to interpreting, analysing and reacting to a given situation. They may incline to pick peculiar strategic choices, such as using force or relying on external alliances, while not opting for a range of others. Decisions and choices are affected by patterns of thinking that evolved over the years. Strategic culture has evolved and generated significant discussion on theoretical frameworks and potential applications in a regional and international security context. Pakistan-India strategic equation is a complex phenomenon, fraught with hostility and mistrust, impregnated with conventional and non-conventional hazards. India views Pakistan as a stumbling block in realising her power ambition, while Pakistan considers India an existential threat. The article analyses the effect of strategic culture on inter-state relations with emphasis on Pakistan-India relations. Unique historical events, geography, the influence of dominant strategic strata and perception biases shape respective strategic cultures. It further analyses strategic culture based on Hofstede's Model, besides pondering upon symbols and philosophical influences. Bibliography EntryAli, Shehzad. 2022. "Strategic Culture and Inter-State Relations: A Case of Pakistan and India." Margalla Papers 26 (1): 121-131.